Play, liminality and Iiterary discourse - Spariosu, Mihai I. (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This study redefines literature as a liminal phenomenon, or as a ludic no man's land that allows access to alternative realities. After sketching a brief history of the notion of liminality in Western literary theory the study reviews current philosophical concepts of actual, possible, and fictional worlds and -proposes an alternative way of considering literary productions in terms of liminal worlds. The liminal nature of a literary work enables it to propose new sets of values that are incommensurable with those of the community from which it arises and to which it is addressed; in turn, upon receiving the literary work, the community might respond by adopting and even actualizing so me of these sets of values.
Keywords: Play; liminality; literary discourse; fictional worlds